2017
DOI: 10.25181/jppt.v14i1.136
|View full text |Cite
|
Sign up to set email alerts
|

Dinamika Ketenagakerjaan pada Wilayah Pedesaan Lahan Kering di Indonesia

Abstract: PENDAHULUANIndikator tidak langsung tingkat pendapatan rumah tangga sebagai representasi tingkat kesejahteraan di sektor pertanian yang berkaitan dengan tenaga kerja adalah produktivitas tenaga kerja dan tingkat pengangguran. Produktivitas tenaga kerja di sektor pertanian diukur dari pendapatan total yang diperoleh dari seluruh jenis kegiatan yang dilakukan anggota rumah tangga dibagi dengan jumlah anggota rumah tangga yang bekerja. Apabila produktivitas tenaga kerja di sektor pertanian relatif rendah maka sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…Although the gap of land ownership and mastery distribution is one of agricultural development issues revealed frequently, in rural areas this gap will lead to the gap of income distribution. It is because the rural household income derives largely from farming activity in which the land is the main production factor [2]. From the table, it can be seen that the land mastery status by ownership in 15 (fifteen) villages in Andong Sub District is dominated by land-owning farmers who work on the land themselves (73.33 percent), while the rests are farm workers (26.67 percent).…”
Section: Land Mastery Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the gap of land ownership and mastery distribution is one of agricultural development issues revealed frequently, in rural areas this gap will lead to the gap of income distribution. It is because the rural household income derives largely from farming activity in which the land is the main production factor [2]. From the table, it can be seen that the land mastery status by ownership in 15 (fifteen) villages in Andong Sub District is dominated by land-owning farmers who work on the land themselves (73.33 percent), while the rests are farm workers (26.67 percent).…”
Section: Land Mastery Statusmentioning
confidence: 99%
“…Land ownership is important not only to farming, but also to determining a variety of other needs in societal life; thus land functions not only as a productive asset, but also as trading commodity. It makes land an asset and a commodity all at once that can be handed over or can be transferred for its mastery status [2]. Land mastery is a system of cultivating land, particularly farmland, either own land or others' land.…”
Section: Introductionmentioning
confidence: 99%
“…A study [13] reported that almost all WNT region fall under dry-climate zone and only 5% land is in wet-climate conditions found in Central Lombok, West Lombok and East Lombok Districts. On the other word, Lombok is more fertile than Sumbawa Island [14]. Given these conditions, farmers adjust this climatic condition by planting dry tolerant and short harvest period commodities such as maize, mung bean and ground peanut.…”
Section: Agroecological Conditions and Cropping Pattern Of Wntmentioning
confidence: 99%
“…Therefore, in an effort to develop a farming business, corn commodities will always be included in the network of commodity agribusiness activities, meaning that success in increasing the cultivation of corn farming cannot be separated from the commodity agribusiness system itself. The development of corn commodities is not all farmers strive for their own consumption, but most farmers direct these efforts to meet market needs [15].…”
Section: Introductionmentioning
confidence: 99%